2016
DOI: 10.14569/ijacsa.2016.070413
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Dimensions of Behaviors Towards E-Commerce in a Developing Country Context

Abstract: Abstract-Customers prefer to shop online for various reasons such as saving time, better prices, convenience, selection, and availability of products and services. The accessibility and the ubiquitous nature of the Internet facilitate business beyond brick and mortar. The web-based businesses are required to understand the consumers' expectations, attitudes, and behavior across the globe and take into consideration of cultural effects. Saudi Arabia has become a highly potential lucrative market for web-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Budaya dan sosial memiliki pengaruh yang besar pada kegunaan, penerimaan, dan kinerja pengguna pada situs E-commerce [22]. Menarik pelanggan dengan menghindari konflik gambar, kosa kata, atau skema warna karena merupakan bentuk dari norma sosial dan budaya akan mempengaruhi minat seseorang terhadap perilaku penggunaan teknologi informasi [23]. Berikut merupakan hambatan yang terdapat pada social & culture barriers yang telah di kelompokkan oleh [10], yaitu: 1) Kurangnya menyadari popularitas dan pemasaran.…”
Section: Social and Culture Barriersunclassified
“…Budaya dan sosial memiliki pengaruh yang besar pada kegunaan, penerimaan, dan kinerja pengguna pada situs E-commerce [22]. Menarik pelanggan dengan menghindari konflik gambar, kosa kata, atau skema warna karena merupakan bentuk dari norma sosial dan budaya akan mempengaruhi minat seseorang terhadap perilaku penggunaan teknologi informasi [23]. Berikut merupakan hambatan yang terdapat pada social & culture barriers yang telah di kelompokkan oleh [10], yaitu: 1) Kurangnya menyadari popularitas dan pemasaran.…”
Section: Social and Culture Barriersunclassified
“…Thousands of local and global networks including private, public, academic, business, and government networks, all provide to the making of the. In research of culture aspect in business to customer e-commerce researcher found various factor involve such as security and privacy, consumer resources, age, lifestyle, attitude, motivation, personality, values, communication and writing style, language option, navigation models, ethics, gender, public policy, advertisement, awareness, human interaction, procedural compatibility, corporate structure, and prior e-commerce (Akhter, 2016); all these factor have their influence in buying decision drive from the local culture (Al-Hamar, Dawson, & Guan, 2010). Some of the studies on the impact of cross-cultural have unveiled major variance among cultures in in buying decision when it comes on online platform.…”
Section: Factors In B2c E-commercementioning
confidence: 99%
“…The current knowledge is not sufficient for firms to reap the advantages of e-marketplaces [31]. Saudi managers often complain that a lack of understanding and research on the implementation of MIS (Management information systems) in the Saudi kingdom resist the adoption of emarketplaces at large scale [32].…”
Section: E-marketplace Adoption and Usagementioning
confidence: 99%